A new method to determine conductivity distribution based on wire-mesh sensor by iteration. (August 2020) - Zhang, Hengwei; Xiao, Yao; Gu, Hanyang
Highlights: The uniformly sensitive volume assumption of WMS will induce a systematic error. This systematic error was corrected by the correction method proposed in this study. The performance of the correction method was evaluated in different situations. The effects of the sub-USV phase distribution on the WMS signal were discussed. Abstract: The wire-mesh sensor (WMS) is a kind of advanced instrument for gas-liquid two-phase flow measurements. In previous research, the sensitive volume was assumed to be uniformly distributed in the cross-section. The received current was assumed to represent the conductivity averaged over a uniform sensitive volume (USV), which is defined by symmetry considerations within the geometry of the electrode grids of the sensor. The void fraction within USV can be further determined based on the conductivity of USV. However, it is unphysical to determine the USV's conductivity by the received current directly, since the true sensitive volume has an irregular shape due to the complexity of the potential field in the WMS. This study proposes an iterative method to determine the normalized conductivity averaged over each USV from the received current of WMS. The iterative method is based on potential field simulations within the electrode geometry of the WMS and an iterative process. To evaluate the performance of the iterative method, different normalized conductivity distributions were pre-defined. The maximum deviation between the pre-defined normalized conductivity and the normalized conductivity value determined by the new method was within 3%, instead of 30% for the conventional method. The performance of the new method for WMSs with different axial distance between transmitter and receiver grids L a was also evaluated. For a larger L a, more iterations need to be carried out to reach this accuracy. The limitation of this iterative method has been discussed. To reconstruct the sub-USV non-conductive phase distribution, the resolution of iterative method should be enhanced to describe the distribution of sub-USV non-conductive phase in future studies.